If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4X + 30 = X + 39 Reorder the terms: 30 + 4X = X + 39 Reorder the terms: 30 + 4X = 39 + X Solving 30 + 4X = 39 + X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 30 + 4X + -1X = 39 + X + -1X Combine like terms: 4X + -1X = 3X 30 + 3X = 39 + X + -1X Combine like terms: X + -1X = 0 30 + 3X = 39 + 0 30 + 3X = 39 Add '-30' to each side of the equation. 30 + -30 + 3X = 39 + -30 Combine like terms: 30 + -30 = 0 0 + 3X = 39 + -30 3X = 39 + -30 Combine like terms: 39 + -30 = 9 3X = 9 Divide each side by '3'. X = 3 Simplifying X = 3
| x+8-5=1 | | 10x=2x-32 | | 24-2x=12 | | 15-6x=-27 | | -9a=45 | | 2x-3=14+2(x-12) | | x/8+7=9 | | 4a+2(4a)=2a-4 | | 5(4+2x)=18-6x | | sin^2x-cos^2x=0 | | -6x-31=-2x+25 | | .5(c+2.8)-c=0.6c+0.3 | | p-4=-8+p | | 4(7+c)=3(c-4) | | (2x+3)-19=x | | (8-v)(2v-1)=0 | | 13y+3x=635 | | 9x^2+4y^2-36=0 | | 5b-30=3+8b+72 | | 20p^2-9p-20=0 | | x^4-x^3-42x^2=0 | | 3x+4=44 | | -9n+5(2+6n)=-7n-18 | | 3x+13y=635 | | 56(3x+7)=180 | | (9x-5)(-6x-4)= | | 5=-2 | | 5m-(m+6)=0 | | -2(-4)+(-18)= | | 18x=28x | | 1x=13 | | 4x-2=x-5 |